Prolonged activity of the transposase helper may raise safety concerns during DNA transposon-based gene therapy - Gergely Imre; Bertalan Takács; Erik Czipa; Andrea Bakné Drubi; Gábor Jaksa; Dóra Latinovics; Andrea Nagy; Réka Karkas; Liza Hudoba; Bálint Márk Vásárhelyi; Gabriella Pankotai-Bodó; András Blastyák; et al. (Molecular Therapy: Methods & Clinical Development, 2023)
DNA transposon-based gene delivery vectors represent a promising new branch of randomly integrating vector development for gene therapy. For the side-by-side evaluation of the piggyBac and Sleeping Beauty systems—the only DNA transposons currently employed in clinical trials—during therapeutic intervention, we treated the mouse model of tyrosinemia type I with liver-targeted gene delivery using both transposon vectors. For genome-wide mapping of transposon insertion sites we developed a new next-generation sequencing procedure called streptavidin-based enrichment sequencing, which allowed us to identify approximately one million integration sites for both systems. We revealed that a high proportion of piggyBac integrations are clustered in hot regions and found that they are frequently recurring at the same genomic positions among treated animals, indicating that the genome-wide distribution of Sleeping Beauty-generated integrations is closer to random. We also revealed that the piggyBac transposase protein exhibits prolonged activity, which predicts the risk of oncogenesis by generating chromosomal double-strand breaks. Safety concerns associated with prolonged transpositional activity draw attention to the importance of squeezing the active state of the transposase enzymes into a narrower time window.